Marital Risk, Family Insurance, and Public Policy - Hans Fehr; Manuel Kallweit; Fabian Kindermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The present paper aims to quantify the growth and welfare consequences of changing family structures in western societies. For this reason we develop a dynamic general equilibrium model with both genders which takes into account changes of the marital status as a stochastic process. Individuals respond to these shocks by adjusting savings and labor supply. Our quantitative results indicate that the declining number of marriages coupled with increasing divorce rates had a profound effect on macroeconomic variables and long-run welfare. We find a significant increase in aggregate capital accumulation and a rising labor market participation of women. In addition, our simulations indicate that the change in the marital structure had significant negative welfare consequences for women who lost between 0.4 and 2.2 percent of aggregate resources. The impact on men's welfare, however, could be positive or negative depending on the specific calibration.
Keywords: J12; J22; 330; family formation; stochastic general equilibrium; life cycle model